DESAIN TAMAN TOGA DI PEKARANGAN RUMAH POSYANDU RW 04 DESA CIBODAS, KECAMATAN PASIR JAMBU, KABUPATEN BANDUNG - Etty Indrawati; Silia Yuslim; Dwi Indrawati; Olivia Seanders (Jurusan Teknik Lingkungan Fakultas Arsitektur Lanskap dan Teknologi Lingkungan, Universitas Trisakti, 2023)
Cibodas Village, Pasir Jambu District, Bandung Regency is an Eco-village that has been fostered through the Ministry of Research, Technology and Higher Education's Grant program. The sustainability of an Eco-village requires the involvement of a healthy local community. One of the efforts implemented through this PkM program is the utilization of Posyandu house yards through planting family medicinal plants (TOGA). The PkM activity aims to provide an example of a TOGA garden design that is beneficial for the local community to be an example in arranging TOGA in their yards. The PkM implementation method begins with a location survey and discussions with representatives of the RW/RT and PKK administrators to obtain an optimal TOGA garden design in the Posyandu RW 04 yard. The implementation was carried out with counseling regarding the design of the TOGA park and the technical construction of it. In addition, to find out the benefits felt from this PkM activity, participants consisting of representatives of RW/RT administrators and PKK administrators were given a pretest and posttest. The pretest results showed that basically the participants already knew TOGA, but did not understand the TOGA arrangement and then the posttest results showed that there was an increase in the participants' understanding of the TOGA garden (100%). However, participants hope to receive assistance in applying garden designs in their yards. Therefore, it is necessary to extend the collaboration between the Faculty of Landscape Architecture and Environmental Technology, Universitas Trisakti and the Head of Cibodas Village, which has expired.